Taxonomical and bionomical notes on the Sicilian endemic water beetle Ochthebius (Cobalius) biltoni (Coleoptera: Hydraenidae) - Simone Sabatelli; Emiliano Mancini; Paolo Audisio (Fragmenta entomologica, 2018)
In this paper we present additional information on taxonomy, ecological preferences and conservation biology of the rare and poorly known Sicilian endemic Ochthebius biltoni Jäch & Delgado, 2017. It represents one of the most outstanding endemic elements of the Sicilian and Italian water beetle fauna.